1986
DOI: 10.1139/f86-078
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Trace Metal Mixtures to American Flagfish (Jordanella floridae) in Soft, Acidic Water and Implications for Cultural Acidification

Abstract: Laboratory exposures over 1.3 generations showed that trace metal mixtures played a dominant role in the reproductive failure of American flagfish (Jordanella floridae) in soft (6.0 mg∙L−1 as CaCO3 total hardness), acidified (pH 5.8) water. This finding may also apply for native fish species inhabiting culturally acidified waters. Reproductive failure was complete when pH 5.8 water contained a mixture of Al, Mn, Fe, Ni, Zn, Cu, and Pb at 57% of the concentrations found in acidified waters (or 0.57 ALC). Fry di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
2

Year Published

1986
1986
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 28 publications
3
34
2
Order By: Relevance
“…However, ovulation was delayed in the acid water group. Delayed time to spawning was recorded for flagfish (Jordanella floridae, Cyprinodontidae; a species not found in acid waters) subjected to acid and heavy metal mixtures, although egg production was unaffected (Hutchinson and Sprague, 1986). Delayed, but not inhibited, spawning of perch (Vuorinen et al, 1992) and ovulation in whitefish (Coregonus wartrnanni, Salmonidae; Vuorinen et al, 1990) has been recorded in acid lakes.…”
Section: Gametogenesis and Spawningmentioning
confidence: 96%
“…However, ovulation was delayed in the acid water group. Delayed time to spawning was recorded for flagfish (Jordanella floridae, Cyprinodontidae; a species not found in acid waters) subjected to acid and heavy metal mixtures, although egg production was unaffected (Hutchinson and Sprague, 1986). Delayed, but not inhibited, spawning of perch (Vuorinen et al, 1992) and ovulation in whitefish (Coregonus wartrnanni, Salmonidae; Vuorinen et al, 1990) has been recorded in acid lakes.…”
Section: Gametogenesis and Spawningmentioning
confidence: 96%
“…Spehar et al (1978) demonstrated that Cd and Zn had a less than additive effect on larval survival of the flagfish Jordanella floridae . Comparisons with studies involving experiments with complex metal mixtures (Hutchinson & Sprague, 1986) are difficult, because it is not known which of the components in the metal mixture caused the observed effects . Comparisons with shortterm experiments ( de March, 1988 ;Thorp & Lake, 1974 ;Herkovits & Peres-Coll, 1991) are difficult, as there may be different mechanisms of toxicity during short and long term exposure.…”
Section: Survivalmentioning
confidence: 99%
“…Few studies have considered the combined effects of metal mixtures on freshwater invertebrates (EIFAC, 1987), whilst fish have been used more often as test organisms (Hutchinson & Sprague, 1986 ;Spehar et al ., 1978 ;Spehar & Fiandt, 1986 ;Enserink et al, 1991) . In particular chronic toxicity studies on the effects of metal mixtures on aquatic organisms are rare (Enserink et al, 1991 ;Kraak et al, 1994) .…”
Section: Introductionmentioning
confidence: 99%
“…Some of these metals are present in concentrations high enough to be toxic to fish in very soft water. At these levels copper and zinc in mixtures with aluminium are lethal to American flagfish, JordanellaJEoridae, a species not found in the affected waters (Hutchinson & Sprague, 1986). Similar concentrations of cadmium (Rombough & Garside, 1984) and manganese can produce sublethal disturbances in salmonids held in soft, acid water.…”
Section: Introductionmentioning
confidence: 99%